Transient Myoclonic State with Asterixis: Primary Motor Cortex Hyperexcitability is Correlated with Myoclonus - Hitomi, Takefumi; Ikeda, Akio; Inouchi, Morito; Fumuro, Tomoyuki; Imamura, Hisaji; Nakagawa, Tomokazu; Matsumoto, Riki; Takahashi, Ryosuke (Internal Medicine, 2011)
Objective To clarify the clinical features and mechanism of the transience of myoclonus in patients with a transient myoclonic state with asterixis (TMA). Methods We investigated the clinical and eletrophysiological profiles of 6 patients with TMA (age: 84±3 years). During an asymptomatic period, somatosensory evoked potentials (SEPs) were recorded in all 6 patients and motor evoked potentials (MEPs) were examined in 1 patient. SEPs were recorded and jerk-locked back averaging (JLA) was performed in 2 patients while symptomatic. SEPs were also recorded from 8 aged control subjects (age: 68±5 years). Results All TMA patients had mild chronic systemic diseases. During an asymptomatic period, SEP amplitudes were not significantly enlarged in comparison with control subjects, and MEPs were normal. Examination of 2 patients during symptomatic period indicated no enlargement of SEP amplitudes and JLA disclosed a positive spike preceding myoclonic jerks. In one of these patients, the amplitude of the positive spike decreased once myoclonus improved. Conclusion TMA occurred in aged patients with mild chronic systemic diseases. JLA findings and the absence of giant SEPs further support that TMA is a cortical non-reflex myoclonus. In addition, transient hyperexcitability at the primary motor cortex disclosed by JLA correlated well with its transient symptoms.